The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/20002297.2017.1374154
|View full text |Cite|
|
Sign up to set email alerts
|

Immunoglobulin G antibodies againstPorphyromonas gingivalisorAggregatibacter actinomycetemcomitansin cardiovascular disease and periodontitis

Abstract: Objectives: The aim was to elucidate whether levels of circulating antibodies to Actinobacillus actinomycetemcomitans and Porphyromonas gingivalis correlate to loss of attachment, as a marker for periodontitis and cardiovascular disease (CVD). Design: Sera were collected from 576 participants of the Danish Health Examination Survey (DANHES). Immunoglobulin G antibodies against lipopolysaccharide (LPS) and protein antigens from the a, b and c serotypes of A. actinomycetemcomitans and P. gingivalis were quantifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 48 publications
1
44
0
Order By: Relevance
“…One marker for SLE is higher IgG CMV levels due to higher risk of infection. 29 Our study also found higher IgG CMV levels, and other systemic conditions such as human immunodeficiency virus (HIV) infection and rheumatoid arthritis. 25,30 It is believed that IgG CMV levels are hallmarks of apoptosis and tissue damage also.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…One marker for SLE is higher IgG CMV levels due to higher risk of infection. 29 Our study also found higher IgG CMV levels, and other systemic conditions such as human immunodeficiency virus (HIV) infection and rheumatoid arthritis. 25,30 It is believed that IgG CMV levels are hallmarks of apoptosis and tissue damage also.…”
Section: Discussionsupporting
confidence: 65%
“…Another study found IgG associated with bacterial periodontitis directly, resulting in a higher prevalence of periodontitis. 29,31 This study also found that IgG CMV levels played a critical role in the regulation of host immune response and inflammation. This pathway can be modulated by various stimuli, including cytokines and immune cells themselves.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…A recent study showed that serum IgG antibodies against periodontal pathogens serve as potential biomarkers that can be used to determine the risk factors for systemic diseases (15,16). Univariable logistic regression analyses have shown serum IgG levels against P. gingivalis to be associated with cardiovascular disease (15).…”
Section: Introductionmentioning
confidence: 99%
“…(36) In addition, cardiovascular disease (CVD) and periodontitis are associated with levels of IgG to P. gingivalis. (37) P. gingivalis IgA levels also predict myocardial infarction and stroke independently of established CVD risk factors. (38) A significant correlation between fibrosis progression and P. gingivalis IgG titers has been reported in a study evaluating the effect of P. gingivalis infection as a risk factor in the progression of NASH.…”
Section: Discussionmentioning
confidence: 96%